Efficient transportation and pavement systems : characterization, mechanisms, simulation, and modeling : proceedings of the 4th International Gulf Conference on Roads, Doha, Qatar, 10-13 November 2008 /: characterization, mechanisms, simulation, and modeling : proceedings of the 4th International Gulf Conference on Roads, Doha, Qatar, 10-13 November 2008. (©2009) - Unknown
No abstract available